Поливная керамика местного производства в золотоордынском Азаке. Краткий очерк - Масловский, А.Н. (Степи Европы в эпоху средневековья, 2012)
This paper considers glaze pottery - the products of one of the two groups of potters who worked in Azak. This paper has briefly reviewed a history of studying glaze pottery. The data on the location of workshops in the town and the peculiarities of manufacturing technology have been provided. Morphological typology and classification of ornaments found on the local glaze pottery have been presented. The paper is well illustrated. A considerable selection of glaze ware of Azak local manufacture is published for the first time.